Computational Fluid Dynamics (CFD) Simulation of Transitioning Slug Flow to Laminar Flow in Horizontal Pipeline - JALALUDIN, MOHD AMIR IZZAT (IRC, 2018)
In oil and gas industries, the horizontal pipeline is a common piping system that been used in distributing two-phase flow. the However, one of the major problems occurs in two-phase flow are the slug flow. The slug generation happens due to the increase in velocity of gas that allows the liquid surface to move upward reach the top of the pipe and form an elongated bubble. It is important to understand the characteristic of slug flow that could affect the pipeline system. The objective of this project is to determine an effective orifice plate geometry to be inserted inside the horizontal pipe to change slug flow to laminar flow using computational fluid dynamic (CFD) and to correlate diameter ratio of orifice plate geometry inside the horizontal pipe. There will be three diameter ratio of orifice plate geometry which was 0.5,0.6 and 0.8 in order to achieve the objective. The simulation of flow pattern was evaluated using FLUENT 18. The volume of fluid (VOF) method and K epsilon was used to obtain the distribution pattern for different flow regime. The validation of present work validated with Baker’s flow map for the diameter of 0.08 m and 8 m length. Finally, the liquid holdup and pressure drop for every diameter ratio was analyzed. The present result shows that diameter ratio of 0.5 produce higher pressure drop thus form bubble flow pattern due to high velocity compared to 0.8 diameter ratio of orifice plate geometry.